De louco e cangaceiro a valente e destemido: as representações sobre o coronel José Pereira na Guerra de Princesa (PB) - Silva, Auricélia Maria da (2020)
The armed movement known as “Princesa war” had as central figures the Colonel José Pereira, political leader of the city of Princesa Isabel (PB), against the rules imposed by the state government of politician João Pessoa. The war breaks out in february and ends with the death of João Pessoa on July 26, 1930. Given the effervescence, the events were narrated daily by the newspapers of the time. In the state of Paraíba, the newspaper A União was the body that gave voice to the current government. In pernambuco, the Jornal do Commercio, its creators were friends and supporters of the princesense colonel. The representations about the colonel, considering the time frame of the municipality's memory corresponding to the “Princesa War”, led by the local political representative, express divergent views regarding his figure. Due to the speeches charged by the two journals, it is necessary to ask: how was the image of Colonel Zé Pereira represented in the periodicals “A União” and “Jornal do Commercio” in 1930? The general objective of this work is to analyze how the image of Colonel José Pereira was constructed in the journalistic vehicles A União and Jornal do Commercio, in the publications of the months of February, March, April, May, June, July and August of the year 1930, from the speeches produced at the time by these media outlets. The research is characterized as qualitative, descriptive, documentary. Its justification is to study the possibilities of critical analysis of information in journalistic content, as well as the use of methodologies of organization, access and use of information in the field of Information Science and application of the method of analysis of the domain of discourse. The aforementioned months of the analyzed newspapers date from February, the beginning of the War, and extends to the month of August. The present work has the reading, rereading and sharing of ideas about the person of Colonel “Zé Pereira”, as well as his political performance in the War. The study found that the domains and content used to represent it in journalistic articles are expressly opposed, since among the terms found, the following words stand out: the word "cangaceiro" which means "criminal, bandit and robber", usually presented by the newspaper A União to refer to José Pereira. On the other hand, the entry "liberator" appears, which expresses "one who frees a person from great danger" and "defender", which represents "one who defends, protector", these being the terms used by Jornal do Commercio. Finally, it is reiterated that Information Science is an indispensable field of knowledge for studies aimed at social representations based on existing information.